MicroRNAs as Novel Regulators of Neuroinflammation - Dominika Justyna Ksiazek-Winiarek; Magdalena Justyna Kacperska; Andrzej Glabinski (Mediators of Inflammation)
MicroRNAs are relatively recently discovered class of small noncoding RNAs, which function as important regulators of gene expression. They fine-tune protein expression either by translational inhibition or mRNA degradation. MicroRNAs act as regulators of diverse cellular processes, such as cell differentiation, proliferation, and apoptosis. Their defective biogenesis or function has been identified in various pathological conditions, like inflammation, neurodegeneration, or autoimmunity. Multiple sclerosis is one of the predominated debilitating neurological diseases affecting mainly young adults. It is a multifactorial disorder of as yet unknown aetiology. As far, it is suggested that interplay between genetic and environmental factors is responsible for MS pathogenesis. The role of microRNAs in this pathology is now extensively studied. Here, we want to review the current knowledge of microRNAs role in multiple sclerosis.